2020
DOI: 10.3389/fimmu.2020.01037
|View full text |Cite
|
Sign up to set email alerts
|

Anti–PD-1/PD-L1 Blockade Immunotherapy Employed in Treating Hepatitis B Virus Infection–Related Advanced Hepatocellular Carcinoma: A Literature Review

Abstract: Hepatitis B virus (HBV) infection is regarded as the main etiological risk factor in the process of hepatocellular carcinoma (HCC), as it promotes an immunosuppressive microenvironment that is partially mediated by the programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) signaling pathway. The tumor microenvironment (TME) of HBV-related HCC is indeed more immunosuppressive than microenvironments not associated with viruses. And compared to TME in hepatitis C virus (HCV) infected HCC, TME of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 94 publications
(118 reference statements)
1
69
0
Order By: Relevance
“…More recently, ADORA1 has been shown to participate in the PD-1 based checkpoint anti-cancer strategy in non-small cell lung cancer (NSCLC). 21 Given the complexity and etiology of viral hepatitis with HCC in China, 22 plus the success exploration on anti-PD-1/PD-L1 blockade immunotherapy in treating Hepatitis B Virus infection-related advanced hepatocellular carcinoma, 23 development of FDA-approved ADORA1 antagonists could light up a bright light in HCC, as well as cancer patient outcome, especially with current PD-1-based multiple immune therapies. 24 submit your manuscript | www.dovepress.com…”
Section: Discussionmentioning
confidence: 99%
“…More recently, ADORA1 has been shown to participate in the PD-1 based checkpoint anti-cancer strategy in non-small cell lung cancer (NSCLC). 21 Given the complexity and etiology of viral hepatitis with HCC in China, 22 plus the success exploration on anti-PD-1/PD-L1 blockade immunotherapy in treating Hepatitis B Virus infection-related advanced hepatocellular carcinoma, 23 development of FDA-approved ADORA1 antagonists could light up a bright light in HCC, as well as cancer patient outcome, especially with current PD-1-based multiple immune therapies. 24 submit your manuscript | www.dovepress.com…”
Section: Discussionmentioning
confidence: 99%
“…In the dose-expansion phase, 6- and 9-month OS rates were 84% and 70% in HBV+ patients, 85% and 81% in HCV+, while for the entire population of the study, 83% and 74%, respectively [ 52 ]. In the CheckMate 459 study (nivolumab vs. sorafenib), a consistent effect on OS was also observed in advanced HCC with nivolumab, and benefit was noted for patients with HBV infection [ 53 , 177 ].…”
Section: Hepatitis Infection and Immunotherapymentioning
confidence: 99%
“…In the phase 3 KEYNOTE-240 study, ORR in the whole population was 18% for pembrolizumab vs. 4% for placebo, while HBV+ patients achieved improved OS in comparison to placebo [HR 0.57 (CI: 0.35–0.94)], while no significant benefit appeared in HCV+ patients [ 55 ]. In the phase III, IMbrave150 study, combination of atezolizumab and bevacizumab prolonged median PFS of HBV+ HCC compared to sorafenib, but this phenomenon did not appear in the population of HCC of non-viral etiology (median PFS, HBV+ HCC: 6.7 vs. 2.8 months; non-viral HCC: 7.1 vs. 5.6 months) [ 177 ].…”
Section: Hepatitis Infection and Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unknown whether virally-induced HCC is more prone to immune attack either secondary to the presence of foreign viral antigens or an immune response to the virus, compared to non-viral associated HCC. A recent pooled analysis assessed the efficacy of anti-PD1 or PDL1 in HBV infected HCC patients in comparison to non HBV infected HCC patients [ 86 ] . The results indicated that patients with HBV infection achieved ORRs similar to their non-infected counterparts, and this was seen with single and multi-agent treatment regimens.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%